Frequency-dependent line model in the time domain for simulation of fast and impulsive transients - Torrez Caballero, Pablo [UNESP]; Marques Costa, Eduardo C.; Kurokawa, Sérgio [UNESP] (Elsevier, 2016)
A new transmission line model is proposed based on the well-established Bergeron method. The conventional Bergeron model is characterized by the line representation by concentrated longitudinal and transversal parameters, i.e., electrical parameters of the line are represented by means of electric circuit elements. The original approach of this research is the inclusion the frequency effect in the longitudinal parameters of the Bergeron line representation. In order to increase the frequency range covered by the proposed model, the line is represented by a cascade of line segments which are modeled following the proposed frequency-dependent Bergeron circuit. The differential equations resulted from the proposed development are represented by state matrices. The line representation by cascade of frequency-dependent Bergeron circuits enables to extend the application of the new modeling technique for simulations considering a wide range of frequencies, from a switching up to an atmospheric impulse. The proposed line model is validated based on results obtained from the well-established line model using numerical Laplace transform.
Keywords: Bergeron method; Electromagnetic transients; Time-domain analysis; Transmission line modeling - TLM